Effect of a spiral phase on a vector optical field with hybrid polarization states. (18th May 2015) - Chen, Rui-Pin; Zhong, Li-Xin; Chew, Khian-Hooi; Gu, Bing; Zhou, Guoquan; Zhao, Tingyu
Abstract: The propagation dynamics of a vector field with inhomogeneous states of polarization (SoP) imposed a vortex is studied using the angular spectrum method. The evolution of SoP in the cross section of the field during propagation is analyzed numerically by the Stokes polarization parameters. The results indicate that SoP in the field cross section rotate along the propagation axis during propagation due to the existence of a vortex. In addition, the interaction between the phase singularity and the polarization singularity leads to the creation or annihilation of the optical field in the central region. In particular, the distributions of the transverse energy flow and both spin and orbital optical angular momentum fluxes in the cross section of the vortex vector optical field depend sensitively on both the vortex and polarization topology charges.